PENERAPAN METODE PROFILE MATCHING PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK DI PT. KARYA ANUGRAH TEKNOLO - Nur Afifah; Ika Kurniawati; Heriyanto Heriyanto (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
PT. Karya Anugrah Teknologi is a retail company that was founded in 2012 with a focus on selling computer equipment, which is located in the West Jakarta area. Every year the company holds a selection of the best employees who will be given rewards and bonuses. The purpose of this study is to create an employee performance appraisal system in order to provide rewards and bonuses for salary increases by analyzing employee data according to predetermined criteria. The process stages in the Profile Matching method used in this study include Gap Mapping, Weighting, Calculation and Grouping of Core and Secondary Factors, Calculation of Total Value, and Calculation of Ranking. The results of this study resulted in recommendations of selected employees based on the ranking calculation of the method used. The employee who is in first place is Eko with a score of 4,925. The results of the recommendation of the best employees based on this calculation are expected to be one of the decision support systems for companies to provide rewards and bonuses for salary increases for the best employees in an objective manner and pay attention to the required aspects.